MODEL MANAJEMEN BERBASIS SEKOLAH - Abd Hafid (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
The existence of the National Constitution on local government contributes to educational management model. The for-mer centralized education has become decentralized. This leads to the growth of school based management. The purpose of this is to em-power human resources, in particular to the head masters, teachers, administrative staff members, students and their parents, and the local community. They are empowered by giving them authority, and flexi-bility to handle the issues faced by the respective school. In short, school based management is more transparent and accountable, com-munity involvement, active, creative, effective and enjoyable learning.